Legal Protection For Users Of Public Transportation Services (Passenger) Based On Law No. 22 Year 2009 - Dian Natalia (Journal of Law Science, 2021)
Transportation or transportation is a very important field of activity in the life of the Indonesian people. However, in reality, transportation drivers often take actions that are considered to cause harm to passengers.The problems raised in this thesis are the legal position of service users (passengers) of public transportation as consumers of public transportation facilities, things that can cause harm to service users (passengers) of public transportation in carrying out transportation, and the form of legal protection provided by Law no. 22 of 2009 to service users (passengers) of public transportation. The writing method that underlies the writing of this thesis is the method of normative research and sociological research. In normative research, the author conducts research through regulations and legal materials related to this writing, while in sociological research, the author conducts research on one of the transportation companies in the city of Pematangsiantar, namely the transportation company CV. Masterpiece. The collection of data in writing this thesis is by library research, namely studying books, laws and regulations, lecture notes and other literature sources related to this thesis and field research, namely research carried out independently. directly to the object of research to collect the necessary data and information. In a carriage agreement, the position of the parties, namely the carrier and the service user, is equal. As for the things that can cause harm to passengers due to the fault of the carrier, among others, accidents caused by negligence of the driver, conditions of transportation that are not suitable for use, or due to lost or damaged passenger luggageThe government should increase the socialization activities of Law no. 22 of 2009, both to public transport operators and to the wider community as users of public transport services, so that legal protection efforts against public transport service users (passengers) as regulated in Law no. 22 of 2009 can actually be implemented by all public transportation companies.